The Building of Economics at Adelaide - Anderson, Kym (University of Adelaide Press, 2009)
The Economics discipline at the University of Adelaide has a distinguished 100 year history of which the University and the State of South Australia can be proud. Very few other departments, of any discipline in Australian universities, could claim to have a majority of its lecturer appointments rising to full Professor status over a period as long as 1901 to 1995. Nor would many other university departments be able to say they have had five of their graduates win Rhodes Scholarships in the past 12 years.